ASSOCIATION BETWEEN NEEDLE SIZE, POSTINJECTION REFLUX, AND INTRAOCULAR PRESSURE SPIKES AFTER INTRAVITREAL INJECTIONS. Issue 7 (July 2015) - Pang, Claudine E.; Mrejen, Sarah; Hoang, Quan V.; Sorenson, John A.; Freund, K. Bailey
Abstract : Purpose: To compare the effect of 30-gauge versus 32-gauge needle size on postinjection reflux and immediate postinjection intraocular pressure (IOPimmed_post ) spikes in eyes injected with anti-vascular endothelial growth factor agents. Methods: This was a prospective interventional case series of 65 eyes of 54 consecutive patients in a clinical practice setting who received intravitreal anti-vascular endothelial growth factor therapy. All eyes had preinjection IOP, IOPimmed_post, postinjection reflux, and axial lengths recorded. Results: There was a higher incidence of postinjection reflux in eyes injected with 30-gauge (53%) compared with those injected with 32-gauge (13%, P = 0.0007). Among 34 eyes injected with 30-gauge, 16 eyes without appreciable postinjection reflux had mean IOPimmed_post of 44.3 ± 7.48 mmHg and mean IOPimmed_post elevation of 29.6 ± 2.10 mmHg, which was significantly higher than the 18 eyes with reflux (mean IOPimmed_post of 18.8 ± 7.15 mmHg and mean IOPimmed_post elevation of 4.5 ± 1.74 mmHg, P < 0.0001). Among 31 eyes injected with 32-gauge, 27 eyes without appreciable postinjection reflux had mean IOPimmed_post of 44.4 ± 10.82 mmHg and mean IOPimmed_post elevation of 29.5 ± 1.99 mmHg, which was significantly higher than the 4 eyes with reflux (mean IOPimmed_post of 21.3 ± 8.54 mmHg and mean IOPimmed_post elevation of 9.5 ± 4.05 mmHg, P < 0.001). The differences in reflux and IOP between the two groups were unrelated to axial lengths ( P = 0.451). Conclusion: Eyes receiving injections with 32-gauge needles had a lower incidence of postinjection reflux and higher mean IOP immediately after injection. Abstract : Eyes receiving intravitreal anti-vascular endothelial growth factor therapy with 30-gauge needles had a higher incidence of postinjection reflux and lower mean intraocular pressure immediately after injection compared with the eyes injected with smaller 32-gauge needles.